Cradle-to-grave life cycle assessment of production and consumption of pulses in the United States. (15th January 2022) - Bandekar, Prathamesh A.; Putman, Ben; Thoma, Greg; Matlock, Marty
Abstract: Environmental impact associated with production and consumption of pulses in the United States was evaluated using life cycle assessment (LCA). The system boundary was set to cradle-to-grave with a functional unit of 60 g (dry basis) of pulses consumed in a US household. Varieties of pulses modeled in the study included field pea (Pisum sativum), lentil (Lens culinaris), chickpea (Cicer arietinum), and dry bean. Three methods of cooking pulses at the consumer stage tested in the study were cooking in open vessel on electric cooking range (OVC), cooking in stovetop pressure cooker on electric cooking range (SPC), and cooking in electric pressure cooker (EPC). OVC formed the base scenario against which all other scenarios were compared. The environmental impact of pulses varied with type of pulse crop, cooking method, and the batch size. Consumption of approximately 60 g of dry pulses resulted in the greatest environmental impact for OVC. The consumer stage contributed at least 83, 81, 76, 75, and 87 percent for global warming potential (GWP), fossil resource scarcity (FRS), water consumption (WC), freshwater eutrophication (FE), and marine eutrophication (ME), respectively for this scenario. EPC resulted in the greatest decrease in the environmental impact, compared to OVC, for GWP, FRS, FE, and ME for all pulse varieties, which was validated in the uncertainty analysis. SPC, on the other hand, decreased the impact across these categories only for chickpea and dry bean. The uncertainty analysis suggested that the differences associated with cooking methods in the mean land use and water consumption scores of pulses were statistically non-significant. The impact categories were also highly sensitive to the mass of pulses cooked in a batch. Increasing the reference flow in OVC to 1 kg decreased the environmental impact of pulses by 49–87 percent for all impact categories, excluding land use. Overall, the study identified the consumer stage as the hotspot for environmental impact in the supply chain of pulses in the United States. The large contribution of the consumer stage to the overall environmental impact of pulses was attributed to electricity consumption for cooking and associated upstream emissions. Highlights: Environmental sustainability of production and consumption of pulses was evaluated. Consumer stage was the hotspot in the supply chain of pulses. Electricity consumption for cooking was identified as the primary contributor. Cooking in pressure cookers was identified as possible impact reduction strategy. Cooking large quantities of pulses can also be adopted for sustainable consumption.